2002
DOI: 10.1007/s004320100294
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor status in female breast cancer: RT-PCR and Western blot studies

Abstract: The high incidence of AR expression in female breast tumours suggests a potential role of AR in breast cancer, in addition to OR and PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
5
32
0
2
Order By: Relevance
“…The effect of flutamide on maspin induction in breast cancer cells simulates that of androgen withdrawal in prostate cancer, because recent studies have identified maspin induction after androgen ablation and/or radical proctectomy (24). It is well documented that contrary to normal breast epithelial cells, breast cancer has a high level of androgen receptor (AR; also observed by us in the archival tissues tested), and the presence of this receptor is associated with high-grade and/or metastatic disease (25,26). By using reverse transcription-PCR analysis, we have also confirmed that MCF-7 cells have a high level of AR with no detectable levels in HMEC1331 cells.…”
Section: Discussionsupporting
confidence: 82%
“…The effect of flutamide on maspin induction in breast cancer cells simulates that of androgen withdrawal in prostate cancer, because recent studies have identified maspin induction after androgen ablation and/or radical proctectomy (24). It is well documented that contrary to normal breast epithelial cells, breast cancer has a high level of androgen receptor (AR; also observed by us in the archival tissues tested), and the presence of this receptor is associated with high-grade and/or metastatic disease (25,26). By using reverse transcription-PCR analysis, we have also confirmed that MCF-7 cells have a high level of AR with no detectable levels in HMEC1331 cells.…”
Section: Discussionsupporting
confidence: 82%
“…The number of AR-positive samples and the level of AR mRNA were significantly higher among the cancer samples than among normal samples. The expression level of both AR gene and AR protein in nuclei was found to be positively correlated with tumor invasiveness (Brys et al 2002). Our study showed that AR had a similar effect as ERα in the up-regulation of LRP16 transcription.…”
Section: Discussionsupporting
confidence: 58%
“…Some studies have focused on the pattern of AR expression in different histological subtypes of breast cancer but the majority of data refer only to ductal carcinomas [7,28]. A strong, consistent AR positivity has been described both in in situ and in invasive apocrine carcinomas as well as in apocrine metaplasia and the intense expression of ARs was often accompanied by a lack of ER and PR immunoreactivity; AR positivity was therefore proposed as a specific marker of apocrine differentiation [15].In one series of invasive breast carcinomas [21], in which ARs were examined, only 14 lobular carcinomas were included; most of these showed an intense AR immunoreactivity.…”
Section: Introductionmentioning
confidence: 99%